Optimal path planning for unmanned air vehicles with kinematic and tactical constraints - Guang Yang; Kapila, V. (Proceedings of the 41st IEEE Conference on Decision and Control, 2002, 2002)
We consider a class of 2D optimal path-planning problems for unmanned air vehicles (UAVs) with kinematic and tactical constraints. The existence of an optimal path class satisfying the UAV kinematic constraints and vector calculus are exploited to reduce this class of optimal path-planning problems to a parameter optimization problem. Illustrative tactical constraints arising in target touring and obstacle avoidance problems are considered. A necessary condition for optimal path planning in the presence of tactical constraints is characterized.. An efficient numerical algorithm using simulated dynamics is developed to enforce the optimality criterion. The proposed optimal path planner can handle multiple tactical constraints. An illustrative numerical simulation demonstrates the efficacy of our approach.